2012
DOI: 10.1371/journal.pone.0048171
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-Associated Phospholipase A2 Activity Predicts Cardiovascular Events in High Risk Coronary Artery Disease Patients

Abstract: ObjectiveLipoprotein-associated phospholipase A2 (Lp-PLA2) is deemed to play a role in atherosclerosis and plaque destabilization as demonstrated in animal models and in prospective clinical studies. However, most of the literature is either focused on high-risk, apparently healthy patients, or is based on cross sectional studies. Therefore, we tested the hypothesis that serum Lp-PLA2 mass and activity are useful for predicting cardiovascular (CV) events over the coronary atherosclerotic burden and conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
2
19
0
1
Order By: Relevance
“…As expected [11], a significant correlation was found between PAF-AH and total cholesterol ( r  = 0.25; p  = 0.032), a stronger direct correlation with LDL ( r  = 0.46, p  < 0.0001) and a highly significant inverse correlation with HDL ( r  = −0.45, p  < 0.0001). No correlation was found with age and sex (15.5 ± 5 nmol/min/ml in females vs. 15.7 ± 3.3 nmol/min/ml in males).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As expected [11], a significant correlation was found between PAF-AH and total cholesterol ( r  = 0.25; p  = 0.032), a stronger direct correlation with LDL ( r  = 0.46, p  < 0.0001) and a highly significant inverse correlation with HDL ( r  = −0.45, p  < 0.0001). No correlation was found with age and sex (15.5 ± 5 nmol/min/ml in females vs. 15.7 ± 3.3 nmol/min/ml in males).…”
Section: Resultssupporting
confidence: 85%
“…Several studies reported a significant association between higher PAF-AH plasmatic activity and the severity of cardiovascular (CV) disease and identified PAF-AH as a marker of vascular inflammation and atherosclerotic plaque instability [911]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in 2 case–control studies, natural deficiency of Lp‐PLA 2 activity due to carriage of the V279F‐null allele in the Lp‐PLA 2 gene was associated with a lower risk of developing CHD 30. In a recent study in European CHD patients, a single‐nucleotide polymorphism of the Lp‐PLA 2 gene was found to be associated with both increased Lp‐PLA 2 activity in plasma and a raised risk of MI 31. Lp‐PLA 2 has also been shown to be highly concentrated in unstable and ruptured atherosclerotic plaques and to be strongly expressed in macrophages in lesions prone to rupture 16.…”
Section: Discussionmentioning
confidence: 99%
“…A study using mice lacking PAF-AH expression suggested that the enzyme may not function in the circulation and that substrate transport to the intracellular compartment may be required before hydrolysis occurs ( 45 ). In addition, the relationship between circulating and tissue PAF-AH and OxPLs has not been critically evaluated, and this issue raises important questions regarding by guest, on April 29, 2019 www.jlr.org Downloaded from Commentary the impact of enzyme, substrate, and products in different biologic compartments. The article by Marathe et al ( 1 ) discusses some of these variables in the intricate biochemistry and biology of PAF-AH, PAF, and related lipids.…”
mentioning
confidence: 99%